Hydraulic analogy and visualisation of two-dimensional compressible fluid flows: part 2: water table experiments. (2018) - Hafez, M.; Jan, F.; Linke, B.; Garretson, I.
In part 1, the theoretical aspects of hydraulic analogy are given in detail. In this part, the water table experiments are reported. Pictures of the flow patterns over different models show the formations of analogous shock waves and expansion fans. Pointed airfoils are tested first. Both biconvex and diamond airfoils are used. Busemann biplane model is included. The formation of a shock over a sharp pointed concave body is also tested. For blunt bodies, flow over a cylinder with a detached bow shock is studied. A sharp and not-so-sharp-spike added to the cylinder and the flow patterns are compared. Shocks inside and outside convergent-divergent nozzles are shown. Also, some results are reported for an experiment with a very simple arrangement of a plate in a plastic container, where the model is fixed, and the water is poured on the plate. Such an arrangement can be used for classroom demonstrations. Issues of manufacturing the models, nozzles and airfoils, are studied as well. Measurement techniques for obtaining quantitative results are briefly mentioned. Finally, concluding remarks about the educational use of this experiment are discussed.